2016
DOI: 10.1186/s13018-016-0433-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination of platelet-rich plasma and bone marrow mesenchymal stem cells enhances tendon–bone healing in a rabbit model of anterior cruciate ligament reconstruction

Abstract: BackgroundThe objective of this study was to investigate the potency of platelet-rich plasma (PRP) combined with bone marrow mesenchymal stem cells (BMSCs) to promote tendon–bone healing in a rabbit model.MethodsIn the in vitro study, the effects of PRP on osteogenic induction of BMSCs were analysed. Later, PRP with or without BMSCs was used in the rabbit model of anterior cruciate ligament reconstruction. Specimens were harvested 8 weeks postoperatively to evaluate tendon–bone healing by histology, radiology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…2 braided wire, and a 10-cm suture was left in the seam as the traction thread. The unilateral knee joint and medial patellar retinaculum were separated in the medial parapatellar approach, but a lateral dislocation was performed to expose the knee joint [16]. After complete removal of the ACL (no remnant preservation for ACL insertion at the top and bottom ends), the anterior drawer and Lachman tests were used to test positive expression.…”
Section: Establishment Of An Acl Reconstruction Model and Rabbit Groumentioning
confidence: 99%
“…2 braided wire, and a 10-cm suture was left in the seam as the traction thread. The unilateral knee joint and medial patellar retinaculum were separated in the medial parapatellar approach, but a lateral dislocation was performed to expose the knee joint [16]. After complete removal of the ACL (no remnant preservation for ACL insertion at the top and bottom ends), the anterior drawer and Lachman tests were used to test positive expression.…”
Section: Establishment Of An Acl Reconstruction Model and Rabbit Groumentioning
confidence: 99%
“…The BMSCs sheet has been proven effective in bone regeneration and can effectively preserve cell-to-cell contact and the extracellular matrix [ 26 ]. In addition, the layered cell sheet may mimic the in vivo bone deposition of bone matrix where osteoblasts are attached on the mineralized sheet [ 16 ]. In this study, The BMSCs sheet can be easily detached from the petri-dish, and more importantly, the SEM results showed that the extracellular matrix as well as cell-cell interactions remain intact.…”
Section: Discussionmentioning
confidence: 99%
“…These growth factors are also important for cell proliferation, differentiation, and neovascularization [ 15 ]. PRP has also been shown to contain cell adhesion molecules and chemotactic properties that attract fibroblasts and mesenchymal stem cells to the repair site [ 16 ]. Therefore, the healing potential of platelets from PRP may be employed to facilitate bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of the application of PRP in anterior cruciate ligament reconstruction in a rabbit model revealed that collagen I, osteocalcin, and osteopontin expression were found to be higher in the BMSC group cultured with PRP than in the PRP group or control group only. More mature and newly formed bone tendon formation is obtained at the bone tunnel walls [19].…”
Section: Effectiveness Of Mesenchymal Stem Cells Therapy In Acl Imentioning
confidence: 99%